The Influence of Services Quality and Facilities on Patient Satisfaction at Wijaya Kusuma Hospital Lumajang, East Java - Wulansari, Retno; Pratama, Muhammad Satria Resa (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This research seeks to determine the influence of services quality on patient satisfaction, and to determine the influence of facilities on patient satisfaction, and to determine the influence of services quality and facilities on patient satisfaction, at Wijaya Kusuma Hospital Lumajang, East Java. This research used a descriptive quantitative methods by using SPSS 26 to process the research data. This research was conducted on patients at Wijaya Kusuma Lumajang Hospital. The sample collection technique used simple random sampling technique. The sample was calculated by using the Slovin formula where 100 respondents were selected. It was found that the partial test (t test) of services quality and facilities have a positive and significant influence on patient satisfaction. The results of simultaneous test (f test) of services quality and facilities have a positive and significant influence on patient satisfaction. Researcher found that 82,9% of independent variables (services quality and facilities) on patients satisfaction and 17,1% was influenced by other variables which not examined As Patient satisfaction has been an important factor to influence them in continuing to visit Wijaya Kusuma Hospital Lumajang in the future, therefore it’s vital to understand why there was reducing number of patients visit to this Hospital in 2020 Year, and which variable influenced to patients satisfaction. Keywords: Service Quality, Facilities, Satisfaction